Understanding Human Behavior: A Review of Psychological Theories and Their Applications - Garg, Rajeshwari (AG Volumes, 2025)
Psychology is a scientific discipline that concentrates on the mind and behaviour, having initially dissociated from philosophy and medicine. It has experienced a lengthy process of acceptance as a separate science. Examine the many works of literature on psychological ideas, human conduct, and its applications in this article. This review highlights the value of diverse psychological theories in understanding and influencing human behavior. Models such as the ARCS model, self-determination theory, expectation-value theory, and goal-orientation theory offer insights into motivation, decision-making, and behavioral maintenance. These theories have practical applications across education, health, and organizational settings—particularly in sustaining behaviors like physical activity, weight loss, and smoking cessation. Understanding cognitive, emotional, and social influences enhances decision-making and promotes healthier behaviors. Emphasizing behavioral maintenance over initiation is vital for long-term outcomes. Overall, integrating these theories provides a strategic framework for developing interventions that support personal growth and societal well-being.